The current paradigm of European Convention of human rights and fundamental freedoms’ rules implementation in criminal law of Ukraine - Кришевич, Ольга Володимирівна; Рощина, Інна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The paper defines the concept of implementation and incorporation of the European Convention norms in the criminal law of Ukraine. The issues of European Convention’s efficiency in the light of its obligation to be implemented in the criminal law of Ukraine, as well as the criteria of national legislation’s conformity to European Convention are determined. Currently there are a lot of problems arising from the introduction of European criminal law convention in Ukraine. Adoption of European Criminal Law Convention in Ukraine is one of the major challenges facing the criminal law of Ukraine. Development of domestic criminal law requires understanding not only of general criminalization of socially dangerous acts based on changes in socio-economic relations in order to increase the effectiveness of the criminal law, to achieve its goals, but also the effective implementation of the European Convention norms in criminal law Ukraine. Today our state and society does not set a utopian goal - to eradicate crime. The existence of crime in society is as objective as an objective existence of the society. In this connection, it is of scientific interest and questions concerning the general efficiency of the criminal law in anticipation of crime. Equally important, of course, is the problem of prediction. To rate actually served as the main criterion for the conclusion responsibility of the subject, it should be dynamic in nature, open system orders with a significant number of degrees of freedom, which allows the best to consider the complexity, organization, relationship objective and subjective- objective factors, the determining human behavior.